Nitrogen sources and splitting in genetically modified maize hybrids - Demari, Gustavo Henrique; Carvalho, Ivan Ricardo; Szareski, Vinicius Jardel; Follmann, Diego Nicolau; Souza, Velci Queiróz de; Basso, Claudir José (Revista de Ciências Agroveterinárias, 2018)
This study sought to evaluate the effects of sources and splitting of nitrogen on the morphological parameters and yield of genetically modified maize hybrids. This study was conducted during 2012/2013 and 2013/2014 growing seasons in Tenente Portela, Rio Grande do Sul, Brazil. Randomized blocks design in factorial arrangement (2 x 2 x 11 x 3) were used for the growing seasons; seasons x maize hybrids x nitrogen management x nitrogen sources, with three replicates. Analysis of variance pointed to interaction between all factors through plant height and number of kernels per row. Significant interaction through season x maize hybrids x nitrogen management for ear insertion height and grain yield. The interaction seasons x nitrogen management x nitrogen sources, and maize hybrids x nitrogen management can be highlighted for the variable ear insertion height. The characteristic thousand grain weight showed interaction through seasons x maize hybrids. Maize hybrids respond similarly to nitrogen management, where different nitrogen sources show similar behavior for the studied variables, without response to grain yield. The different nitrogen management forms caused positive effects on the evaluated variables, especially when performed in the early stages of culture. The current recommendation of nitrogen splitting in maize is adequate, but for the hybrid DKB 250 VT PRO2 ® in water deficit, nitrogen can be applied until the V8 growth stage.